Supply Response Analysis Of Paddy In Kediri : Managerial Implications - Vifi Nurul Choirina; Slamet Hartono; Any Suryantini (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2016)
Research of farmer’s response analysis to price is important to increase paddy production in Kediri. Farmers are conducted as the object of the research because they are the decision maker on all of farming activities. This study is aimed to know the effect of harvest area response, productivity response, supply response paddy, and managerial implications in Kediri. The analysis method used the Nerlove approach through harvest area response and productivity response. Data were collected annually from 1992 to 2015. The result showed that harvest area in previous year was the significant factor to the harvest area. Grain price, fertilizer price index, rainfall, harvest area in previous 2 years and 3 years had no significant effect. Factors which had significant impact for the productivity were grain price and productivity in the previous year, but fertilizer price index, harvest area, and rainfall had no significant effect. Paddy supply-elasticity in short term and long term was inelastic so that supply paddy was unresponsive on grain price changing. Managerial implication formulation consists of procedural implications and policy implications. Procedural implications included the use of a transplanter, jajar legowo system, use of fertilizer in 6 right-ways completed with a demonstration plot. The policy implication is was composed by price and non-price policies. Price policies were showed by costs of good sold which was supported by coopertaion between farmers and BULOG and the use of combine harvester. Non-price policies were embodied with the increasing of cropping index and wetland transformation into settlements.